Growth factors of audit firms in the Republic of Serbia in the period 2018 – 2022 - Peštović, Kristina; Medved, Ivana; Vuković, Bojana; Tica Ilić, Teodora (Anali Ekonomskog fakulteta u Subotici, 2026)
The aim of paper is to investigate the growth of audit firms in the Republic of Serbia during the period 2018 – 2022. Growth was measured as a change in revenue over a fixed period of time. The results indicate that there is significant increasing of audit firms performances measured by sales growth in 2019, and than decreasing in 2020, while in the following years there is increasing of business performance. In order to investigate which factors affect the sales growth rate, regression analysis was conducted. Sales growth was defined as dependend variable, while as independent variable were defined return on assets, current ratio, leverage and corona period as a proxy variable. The results indicate that significant impact on sales growth of audit firms have return on assets, current ratio and corona period. Return on assets and current ratio are significant positive related to sales growth, while corona period is negative related to sales growth. The research results indicate to the profile of audit firms specialy from the perspective of growth facotrs. The results can be of interest for managers and owners of audit firms, profesional audit organizations and other in the process of business decisions making.